Prospects of Nuclear Power Development in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article discusses the current state, problems and prospects for the development of nuclear energy in Uzbekistan. A brief analysis of global trends in the field of nuclear energy, decarbonization processes and increasing importance of renewable energy sources is presented. The special role of nuclear energy in ensuring energy independence in the context of transition to renewable energy sources is noted. The importance of the development of this industry for the future of Uzbekistan is emphasized. The new energy transition is one of the pressing modern trends in the global economy. The need to increase the utilization of low- and no-carbon energy sources, in particular renewable energy sources (RES), is now a priority for the modern energy industry .At present, the drive by developed countries to decarbonize the global economy in order to reduce their dependence on energy imports is creating all sorts of prospects for further development. The need for energy supply has almost quadrupled in the last fifty years. Renewable energy is a real new opportunity.